Technology assessment of elite sports. A systems theoretical approach to doping of the next society - Körner, S. (Athens Journal of Sport, 2014)
In hardly any other part of modern society the idea of "pushing the boundaries" is as obvious and concrete as in modern elite sports: in competitive sports the boundaries of today regularly turn into the mediocrity of tomorrow. In some disciplines like cycling, 100 meter sprint or pole vault we can observe rates of performance enhancement between 24 and 221 percent since the first modern Olympic Games in Athens 1896 (Nature Materials, 2012, p. 651). As such, performance enhancement is a well-known phenomenon in elite sports, and not at least a question of technology (Fuss, Subic & Mehta, 2010). However, some technologies and methods are prohibited and sanctioned as doping. Doping is currently negotiated as the crisis of modern sports -by developing a dynamic of communication that is typical for crisis. In theoretical distance to moral judgement and public scandalization the contribution questions the doping of the next society. It is argued that doping in elite sports is highly functional and as such structurally expectable. After giving a brief description of main structural features of modern elite sports, doping will be illustrated as "functional illegality" (Luhmann, 1976). By addressing molecular target points, especially gene doping is associated with serious consequences for modern sports and society. Focussing on the future of doping the role of another risky technology has to be considered: the internet.